2021
DOI: 10.1186/s42523-021-00149-6
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiome composition, not alpha diversity, is associated with survival in a natural vertebrate population

Abstract: Background The vertebrate gut microbiome (GM) can vary substantially across individuals within the same natural population. Although there is evidence linking the GM to health in captive animals, very little is known about the consequences of GM variation for host fitness in the wild. Here, we explore the relationship between faecal microbiome diversity, body condition, and survival using data from the long-term study of a discrete natural population of the Seychelles warbler (Acrocephalus sech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 121 publications
(178 reference statements)
2
38
1
Order By: Relevance
“…Previous studies have shown that physiological stress can decrease microbial diversity [ 21 ] and both stress and poor body conditions have been connected to microbial dysbiosis [ 15 , 22 ]. Changes in microbial diversity and community dysbiosis have also been associated with lower survival rates [ 23 26 ]. Further, although age- and sex-related variation in microbiota composition is commonly reported for birds (e.g., [ 14 , 24 , 27 , 28 ]), details about such effects are still missing in the context of bird migration.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that physiological stress can decrease microbial diversity [ 21 ] and both stress and poor body conditions have been connected to microbial dysbiosis [ 15 , 22 ]. Changes in microbial diversity and community dysbiosis have also been associated with lower survival rates [ 23 26 ]. Further, although age- and sex-related variation in microbiota composition is commonly reported for birds (e.g., [ 14 , 24 , 27 , 28 ]), details about such effects are still missing in the context of bird migration.…”
Section: Introductionmentioning
confidence: 99%
“…This is necessary to identify plausible drivers (e.g., tooth wear, immunosenescence) and fitness consequences (e.g., muscle loss, declining energy balance constraining fertility) of age-related changes in gut bacterial composition. The possibility that gut bacterial composition exhibits terminal senescence [ 80 ], independent of age, has not been investigated in this or previous studies on mammals due to lack of data on individual survival and remains open…”
Section: Discussionmentioning
confidence: 99%
“…Finally, as not all offspring survived to the end of the experiment, the results may also be affected by selective mortality. Differential abundance of gut bacteria has been linked with survival (Akbar et al, 2021;Worsley et al, 2021). If gut microbiota affected the survival of young voles, then only the voles with the most appropriate microbiota (e.g., matching the evolved metabolic needs) would have been sampled.…”
Section: Reinforced E Ect Of Selection On Microbiota Of Field-reared ...mentioning
confidence: 99%